Pengaruh Budaya dan Sosial dalam Pengembangan Desain Batik Langgam Medan - Damanik, Raudhotul Jannah; Fitri, Hadiani; Hardiansyah, Muhammad Ricky (Medan Resource Center, 2025)
This study employs qualitative methods with a historical approach to analyze the influence of culture and society on the development of Batik Langgam Medan design. The historical approach is used to systematically collect and evaluate data related to past events that have shaped the evolution of Batik Langgam and its future potential. The findings reveal that Batik Langgam was established in 2008 by Hj. Rafika Johani, S.Ag., with the name